Struktur Cosmos Masyarakat Batak dalam Simbol Ulos - Darwin Herlis Manurung; Izak M. Lattu; Rama Tulus (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
This article will discuss about ulos as a symbol of sacred objects. According to the ancestors' beliefs, all lives of Batak people can be read on a piece of ulos cloth. The ulos woven decoration is an expression of prayer and hope for the Creator. Giving ulos correctly is determined by one's position and social status in society. This research was conducted in the Lumban Village of Suhi-Suhi, Samosir Regency. The method used is qualitative with interview, observation, and literature study techniques. The results of the study found that the ulos weavings became the identity of the Batak Toba people who described the cultural messages of the community that were not contained in written texts. In the life rituals of the Toba Batak people. From birth, marriage, until death, Toba Batak people cannot be released from ulos. The ulos symbol can show one of the concept of a sacred appearance. This paper provides advice to traditional leaders, community leaders in order to maintain the sacredness of ulos as a symbol of cosmology that must be preserved.